Student Perspectives on Barriers to Timely Graduation - Kim, Juhee (International Research in Education, 2022)
This study examines the barriers preventing students from graduating college in four years and proposes strategies for enhancing student academic completion and retention in higher education. To explore contemporary perspectives, Appreciative Inquiry was employed. The findings revealed the personal and institutional level of challenges as well as the need for a support system to ensure timely graduation. Addressing students’ biggest barriers to timely graduation require campus-wide engagement and deep collaboration across institutional functions. Specifically, higher education institutions need to provide adequate academic, social, and cultural assistance to embrace international, minority, low-income, and first-generation college students.